Evaluation of the Uganda Social Assistance Grants for Empowerment (SAGE) Programme - Haynes, Alastair (2017)
"As part of the implementation of the Expanding Social Protection programme (ESPP) the Ugandan government aims to reduce chronic poverty and improve life chances for poor people. The Uganda Social Assistance Grants for Empowerment (SAGE) pilot programme is a key element of the ESPP and tests a range of implementation modalities to determine an efficient, cost-effective and scalable social transfer". (...)